Epstein-Barr Virus and Systemic Autoimmune Diseases - Houen, Gunnar; Trier, Nicole Hartwig (Frontiers in Immunology, 2021)
Epstein-Barr Virus (EBV) is an extremely successful human herpes virus, meaning that it infects essentially all human beings at some time during their life span. EBV infection and the associated immune response results in production of antibodies (seroconversion), which occurs mainly during the first years of life, but may also happen during adolescence or later in life. Infection of adolescents can result in infectious mononucleosis, an acute serious condition characterized by massive lymphocytosis. Transmission of EBV mainly occurs through saliva but can rarely be spread through semen or blood, e.g. through organ transplantations and blood transfusions. EBV transmission through oral secretions results in infection of epithelial cells of the oropharynx. From the epithelial cells EBV can infect B cells, which are the major reservoir for the virus, but other cell types may also become infected. As a result, EBV can shuttle between different cell types, mainly B cells and epithelial cells. Moreover, since the virus can switch between a latent and a lytic life cycle, EBV has the ability to cause chronic, relapsing/reactivating infections. Chronic or recurrent EBV infection of epithelial cells has been linked to systemic lupus erythematosus and Sjögren’s syndrome, whereas chronic/recurrent infection of B cells has been associated with rheumatoid arthritis. Accordingly, since EBV can shuttle between epithelial cells and B cells, the systemic autoimmune diseases often occur as overlapping syndromes with symptoms and characteristic autoantibodies (e.g. antinuclear antibodies and rheumatoid factors) reflecting epithelial and/or B cell infection.